Design and Construction of a Reactor Device for (Thermal Catalytic Cracking) of Waste Cooking Oil - Alsarah, Danil Son; Yerizam, Muhammad; Ekawati, Linda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
His study discusses the design and development of a thermal catalytic cracking reactor for converting waste cooking oil into bio-oil as an alternative renewable energy source. The reactor is designed with a semi-batch system equipped with an electric heater, a stirring motor, and a circulation pump. The catalyst used is Ni/Al₂O₃ with a mass of 2.4 grams, and the input volume of waste cooking oil is 2000 mL. The cracking process was carried out at temperatures ranging from 150°C to 250°C for a duration of 4 hours. Experimental results show that the bio-oil yield increased with temperature, reaching the highest yield of 780 mL at 250°C. The total electrical energy consumed by the device was 6,004,800 Joules, while the thermal energy used in the reaction process was 1,221,000 Joules. The energy efficiency of the system was calculated to be 20.33%. These results indicate that the reactor is capable of performing thermal conversion with moderate efficiency and has the potential for improvement through better thermal insulation and heat distribution systems.